2005
DOI: 10.2134/agronj2005.0556
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Cotton and Beef Production to Reduce Water Withdrawal from the Ogallala Aquifer in the Southern High Plains

Abstract: planted annually, primarily in monoculture systems (TASS, 2002). Furthermore, about 5.5 million stocker Agriculture in the Texas High Plains depends heavily on irrigation cattle (about 25% of U.S. total; TASS, 2002; USDA with water withdrawn from the Ogallala aquifer at nonsustainable rates. Our hypothesis was that integrating crop and livestock systems Natl. Agric. Stat. Serv., 2003) are shipped into the High would reduce irrigation water use, maintain profitability, and diversify profitability, and impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 11 publications
5
108
0
Order By: Relevance
“…After upland rice harvesting, perennial forage, such as Panicum maximum, Brachiaria brizantha or B. ruziziensis, could be introduced to achieve a great amount of cover crop in the beginning of the following rainy season and to cultivate another cash crop. Allen et al (2005) observed a higher cotton yield under forage species than cotton monoculture. Kluthcouski et al (2000) obtained higher corn, soybean and common bean yields using straws of Panicum maximum and B. brizantha.…”
Section: Upland Rice Yieldmentioning
confidence: 90%
“…After upland rice harvesting, perennial forage, such as Panicum maximum, Brachiaria brizantha or B. ruziziensis, could be introduced to achieve a great amount of cover crop in the beginning of the following rainy season and to cultivate another cash crop. Allen et al (2005) observed a higher cotton yield under forage species than cotton monoculture. Kluthcouski et al (2000) obtained higher corn, soybean and common bean yields using straws of Panicum maximum and B. brizantha.…”
Section: Upland Rice Yieldmentioning
confidence: 90%
“…where potential ADG is a maximum potential value of ADG, which we set at 0.86 kg/day, slightly lower than the observed maximum season-long values for steers grazing OWB and small grains [17], since small grains are higher quality than OWB.…”
Section: Cattle Growthmentioning
confidence: 95%
“…The Southern High Plains (SHP) of North America was covered by grasses and grazed by wild herbivores before European settlement converted much of the land to annual crops, and returning Southern High Plains land to perennial grasses is compatible with objectives of soil and water conservation [1]. The perennial grass, "WW B. Dahl", an old world bluestem (OWB), has been used for this purpose [1], and is well-suited for dryland cultivation on the Southern High Plains [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations